Mineral nutrition of sugarcane irrigated with sewage effluent in an area with phosphogypsum application - Blum, Julius; Melfi, Adolpho José; Montes, Célia Regina (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to quantify input and removal of nutrients of sugarcane crop systems irrigated, or not, with treated sewage effluent (TSE), with or without phosphogypsum application, as well as to evaluate the effects of these crop systems on plant mineral nutrition status. The evaluated treatments were nonirrigated, and irrigated at 100 and 150% of crop water demand. Phosphogypsum treatments were applied on a third‑harvest sugarcane area, irrigated with TSE since planting. The evaluations were done during two crop seasons. Sugarcane yield was not affected by the treatments. There was a synergic effect on nitrogen and sulfur contents of plants in the treatment with TSE and phosphogypsum. TSE improved plant nutrition as to phosphorus, but it did not as to potassium and sulfur. Iron, zinc, and manganese nutrition was not affected by these micronutrient inputs by TSE. Phosphorus and nitrogen from TSE irrigation should be considered for fertilization recommendations. However, potassium, sulfur, iron, zinc and manganese present in the effluent are not efficient sources of nutrients for plants.